BMI and WC cut offs for the risk of comorbidities of obesity in a population in Indonesia (Faculty of Medicine Universitas Indonesia, 2004)
Over the last few years health care providers have become more aware of the consecquences of obesity as well as the comorbidities of obesity. The body mass index (BMI) and waist circumference (WC) became universally accepted measures to determine the degree of overweight. it is necessary to have cut off points for BMI and WC for the risk factors of the comorbidities of obesity in Indonesia. This study has a cross sectional design with a total of 6318 subjects, that comprised of 5216 males (82.6%) and 1102 females (17.6%). The highest percentage of comorbidities both in males and females were high cholesterol and triglyceride level. The risks of comorbidities were increased at BMI 24.38 kg/m2 and WC 86.25 cm for fasting blood glucose and BMI 24.91 kg/m2 and WC 89.25 cm for triglyceride level. (Med J Indones 2004; 13: 241-5)